2012
DOI: 10.1890/120059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated carbon dioxide and increased temperature on methane and nitrous oxide fluxes: evidence from field experiments

Abstract: Climate change could alter terrestrial ecosystems, which are important sources and sinks of the potent green‐house gases (GHGs) nitrous oxide (N2O) and methane (CH4), in ways that either stimulate or decrease the magnitude and duration of global warming. Using manipulative field experiments, we assessed how N2O and CH4 soil fluxes responded to a rise in atmospheric carbon dioxide (CO2) concentration and to increased air temperature. Nitrous oxide and CH4 responses varied greatly among studied ecosystems. Eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(142 citation statements)
references
References 51 publications
9
131
1
1
Order By: Relevance
“…Yang et al, 2013). This may reflect the fact that water table drawdown increases the area over which CH 4 oxidation takes place (Roulet et al, 1993) and the fact that drawdown can make soil less anaerobic, decreasing CH 4 production by methanogens (Dijkstra et al, 2012). Studies have also shown that water table drawdown can alter vegetation communities, especially in areas abundant in aerenchymatous plants, leading to lower CH 4 emissions (Laine et al, 2009;Yrjala et al, 2011).…”
Section: Environmental Factors Controlling Ch 4 Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al, 2013). This may reflect the fact that water table drawdown increases the area over which CH 4 oxidation takes place (Roulet et al, 1993) and the fact that drawdown can make soil less anaerobic, decreasing CH 4 production by methanogens (Dijkstra et al, 2012). Studies have also shown that water table drawdown can alter vegetation communities, especially in areas abundant in aerenchymatous plants, leading to lower CH 4 emissions (Laine et al, 2009;Yrjala et al, 2011).…”
Section: Environmental Factors Controlling Ch 4 Emissionsmentioning
confidence: 99%
“…Soil warming appears to exert complex effects on CH 4 emissions in peatlands (Dijkstra et al, 2012), with some researchers reporting a positive relationship between warming and CH 4 emissions (Gao et al, 2011;Parrenin et al, 2013;Turetsky et al, 2008) and others reporting a negative relationship (Eriksson et al, 2010). In most peatlands, water table showed a greater effect on CH 4 emissions than direct warming (Turetsky et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Field level experiments revealed the highly variable effects of CO 2 fertilization on N 2 O emissions. Based on a meta-analysis, van Groenigen et al (2011) suggested that elevated CO 2 significantly increased N 2 O emission by 18.8 %, while Dijkstra et al (2012) argued for a non-significant response in non-N-fertilized studies. In contrast to observation studies, the global C-N cycle model analyses from O-CN suggested negative CO 2 fertilization effects on N 2 O emissions .…”
Section: Co 2 and Temperature Responsesmentioning
confidence: 99%
“…However, although denitrification is being considered the dominant mechanism of ecosystem NO 3 -loss (Fang et al, 2015), most field experiments have not found decreases in N 2 O emissions under eCO 2 . Positive or neutral responses 5 have been common, primarily obtained in temperate or boreal forests or grasslands (Van Groeningen et al, 2011;Dijkstra et al, 2012). It should be noted that none of these field experiments were conducted in the tropics, which may hamper comparisons (Huang and Gerber, 2015), also seeing how a substantial portion of our obtained N loss decrease was observed in these latitudes (Fig.…”
Section: Discussionmentioning
confidence: 73%